Degradación y adsorción del colorante AZO RR239 en solución acuosa, por partículas de hierro “zero-valente” a nanoescala, inmovilizadas sobre aserrín (2010)
ABSTRACT: Carra sawdust pretrated with formaldehyde was used to adsorb RR239 (reactive azo dye) at varying pH and zerovalent iron (ZVI) dosage. Modeling of kinetic results shows that sorption process is best described by the pseudosecond-order model. Batch experiments suggest that the decolorization efficiency was strongly enhanced with the presence of ZVI and low solution pH. The kinetics of dye sorption by mixed sorbent (5 g of sawdust and 180 mg of ZVI) at pH 2.0 was rapid, reaching more than 90% of the total discoloration in three minutes.